2021
DOI: 10.1007/s11042-021-11723-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of natural user interface and graphical user interface for narrative in HMD-based augmented reality

Abstract: Over the years, the various mediums available for storytelling have progressively expanded, from spoken to written word, then to film, and now to Virtual Reality (VR) and Augmented Reality (AR). In 2016, the cutting-edge Head-Mounted Display (HMD) AR Microsoft HoloLens was released. However, though it has been several years, the quality of the user experience with narration using HMD-based AR technology has been rarely discussed. The present study explored interactive narrative in HMD-based AR regarding differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…As reported by [51], the AR UI that is supplemented with unnecessary information has confused the users and has caused them to have problems to understand the features. This is also supported by [52] who conducted a study on graphical user interface, which found that some of the users have reported funny or negative feelings when using the AR mobile applications, and the design may give users confusion with the unsuitable visual cues displayed on the mobile screen. The limited screen size of a mobile devices also plays a role in triggering user negative emotions, if the screen is cluttered or improperly designed [31], [47].…”
Section: B User Experience In the Augmented Reality Contextmentioning
confidence: 74%
See 1 more Smart Citation
“…As reported by [51], the AR UI that is supplemented with unnecessary information has confused the users and has caused them to have problems to understand the features. This is also supported by [52] who conducted a study on graphical user interface, which found that some of the users have reported funny or negative feelings when using the AR mobile applications, and the design may give users confusion with the unsuitable visual cues displayed on the mobile screen. The limited screen size of a mobile devices also plays a role in triggering user negative emotions, if the screen is cluttered or improperly designed [31], [47].…”
Section: B User Experience In the Augmented Reality Contextmentioning
confidence: 74%
“…The limited screen size of a mobile devices also plays a role in triggering user negative emotions, if the screen is cluttered or improperly designed [31], [47]. Hence, [51], [52] has suggested to use proper and only necessary visual design elements in AR design. Therefore, there is a need to explore the possible design components for the AR-based mobile application design that can foster positive emotions and user experience.…”
Section: B User Experience In the Augmented Reality Contextmentioning
confidence: 99%
“…Stuart Jeffrey (2015) describes the latter as a field which engages with modes of co-production, physical replication and aesthetic quality, authenticity (Jeffrey et al, 2017), and the complex entanglements of its own production (Huvila, 2012). A majority of practice-oriented XR scholarship focuses on user experience (Wither et al, 2010;Herbst et al, 2008;Hussein & Ali, 2022), technological experimentation (Cavallo et al, 2016;Jin et al, 2021;Shin et al, 2021;Hartmann & Vogel, 2021), pedagogical efficacy (Smørdal et al, 2016;Georgiou & Kyza, 2021;Remolar et al, 2021;Ibharim et al, 2021), or the "placeproducing dimensions of an experience-driven application" (Engberg, 2017, p.3). As an emerging field, a majority of studies involving XR are experimental but also, as Marcos Llobera (2012) notes, limited by the pixels and soundbites which constitute their virtual presence.…”
Section: Xr X Uk Museums X Colonialitymentioning
confidence: 99%
“…Argument realism is the term for a 2D or 3D virtual interface that improves our view of the outside world by superimposing digital content (more information) on top of it. Because we can always see the real world around us, true immersion in the virtual world is not possible [19].…”
Section: Argument Realitymentioning
confidence: 99%